Role of sequence evolution and conformational dynamics in the substrate specificity and oligomerization mode of thymidylate kinases. Issue 10 (27th July 2017) - Biswas, Ansuman; Jasti, Subbarao; Jeyakanthan, Jeyaraman; Sekar, Kanagaraj
Abstract : Thymidylate kinase (TMK) is a key enzyme for the synthesis of DNA, making it an important target for the development of anticancer, antibacterial, and antiparasitic drugs. TMK homologs exhibit significant variations in sequence, residue conformation, substrate specificity, and oligomerization mode. However, the influence of sequence evolution and conformational dynamics on its quaternary structure and function has not been studied before. Based on extensive sequence and structure analyses, our study detected several non-conserved residues which are linked by co-evolution and are implicated in the observed variations in flexibility, oligomeric assembly, and substrate specificity among the homologs. These lead to differences in the pattern of interactions at the active site in TMKs of different specificity. The method was further tested on TMK from Sulfolobus tokodaii (StTMK) which has substantial differences in sequence and structure compared to other TMKs. Our analyses pointed to a more flexible dTMP-binding site in StTMK compared to the other homologs. Binding assays proved that the protein can accommodate both purine and pyrimidine nucleotides at the dTMP binding site with comparable affinity. Additionally, the residues responsible for the narrow specificity of Brugia malayi TMK, whose three-dimensional structure is unavailable, were detected. Our study provides a residue-level understanding of the differences observed among TMK homologs in previous experiments. It also illustrates the correlation among sequence evolution, conformational dynamics, oligomerization mode, and substrate recognition in TMKs and detects co-evolving residues that affect binding, which should be taken into account while designing novel inhibitors.